2017
DOI: 10.1093/hmg/ddx210
|View full text |Cite
|
Sign up to set email alerts
|

Review: placental biomarkers for assessing fetal health

Abstract: The placenta is a multifunctional organ that regulates key aspects of pregnancy maintenance and fetal development. As the placenta is in direct contact with maternal blood, cellular products (DNA, RNA, proteins, etc.) from the placenta can enter maternal circulation by a variety of ways. The application of serum proteins and circulating placental derived DNA has been well demonstrated for the diagnosis of aneuploidy, and there is great interest in exploring the use of placental biomarkers for the prediction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 79 publications
1
30
0
2
Order By: Relevance
“…42 It has been demonstrated that the maternal environment determines the structure and function of the placenta, with consequences on the development of the foetus. 43,44 In the present study, we observed an increase in the expression of NTF4 in the placenta of very active mothers as an adaptive response to maternal physical activity. NTF4 is related to placental growth and inhibition of apoptosis promoting the survival of placental cells.…”
supporting
confidence: 61%
“…42 It has been demonstrated that the maternal environment determines the structure and function of the placenta, with consequences on the development of the foetus. 43,44 In the present study, we observed an increase in the expression of NTF4 in the placenta of very active mothers as an adaptive response to maternal physical activity. NTF4 is related to placental growth and inhibition of apoptosis promoting the survival of placental cells.…”
supporting
confidence: 61%
“…Serial maternal blood sampling is routine in medical care and research. Maternal blood enables direct measures of maternal factors, foetal‐derived material (eg cell‐free nucleic acids, foetal cells) and placenta‐derived material (eg nano‐sized extracellular vesicles, microvesicles, exosomes) . Material leftover from prenatal testing can be studied .…”
Section: Resultsmentioning
confidence: 99%
“…Maternal blood enables direct measures of maternal factors, foetal-derived material (eg cell-free nucleic acids, foetal cells) 58,59 and placenta-derived material (eg nano-sized extracellular vesicles, microvesicles, exosomes). 60,61 Material leftover from prenatal testing can be studied. 63,64 At delivery, cord blood can be sampled and placentas can be measured and studied.…”
Section: Biospecimen Procurementmentioning
confidence: 99%
“…In our study, we were successful in confirming some of our array-wide DNAm findings by an alternate technology and validating these DNAm results in an independent set of samples. These DNAm alterations may be useful in the development of biomarkers for rapid prenatal detection of aCA if they are also detectable in maternal blood [ 79 ], as has been shown for other conditions including cancer [ 80 – 83 ] and preeclampsia [ 84 , 85 ]. However, the aCA-associated methylation changes reported in this study were small in magnitude and may require highly sensitive detection methods.…”
Section: Discussionmentioning
confidence: 99%